Strategy of the US toward Central Asia - Ф. T. Кукеева; Т. Ормышева (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì, 2016)
Authors consider strategic cooperation of the USA and the Central Asian states in modern international relations. The article mainstreams interaction between countries in new geopolitical conditions. Authors give the basic attention to aspects of democratization, human rights and influence of globalization on education structure of the states in the region.